The Role of Corporate Parent Support for Spinoff Innovation Performance - Abou Lebdi, Nabil (Senate Hall, 2017)
Spinoff innovation performance and its prerequisites is a relatively under-researched domain. Despite the innovative drive and remarkable growth rates that spinoffs exhibit, the majority of spinoff research focuses on stock market performance, board composition or simply growth in terms of revenues or employees. The empirical analysis in this paper combines two largely uncharted topics in spinoff research. First, it measures the innovation performance of the spinoff by utilizing product innovation as a key variable. Second, innovation performance is analyzed with regard to the level of corporate parent support. Results from a German startup sample show that obstructive interference by a corporate parent is positively associated with innovation performance of a spinoff - especially compared to spinoffs that receive parent support. Moreover, the analysis reveals that results are mainly driven by high-tech industry branches. Keywords: spinoffs, innovation performance, parent support
Keywords: spinoffs|innovation performance|parent support